EDUCATIONAL PROGRAMS FOR CHINESE CALLIGRAPHY TEACHERS AS A COMPONENT OF QUALITY EDUCATION IN CHINESE UNIVERSITIES (ON THE EXAMPLE OF SHANXI INSTITUTE OF APPLIED SCIENCES AND TECHNOLOGY) - Honghao, Yang (Problems of Engineer-Pedagogical Education, 2023)
The article takes into account the problems existing in the current situation of Chinese calligraphy teacher training, through the research and analysis of a practical example, from the perspective of curriculum setting for analysis. This paper discusses the necessity of curriculum reform in improving the training of Chinese calligraphy teachers. And pointed out the general direction of curriculum reform. An example analyzed by the article is the professional curriculum setting of the calligraphy major of the Academy of Fine Arts of Shanxi University of Applied Science and Technology. The author worked for two years in the calligraphy department of this university. The author is also familiar with the curriculum of calligraphy majors in other Chinese universities. For example, Shanxi Normal University, Shanxi University, Taiyuan Normal University and so on. Although they are slightly different in the curriculum of calligraphy majors, the general construction ideas are exactly the same. In order to explain the problem clearly and to limit the space, a most representative example is deliberately selected, and this example is also the most familiar to the author.The author also discovered the problems existing in the process of calligraphy teacher training during the teaching period of Shanxi University of Applied Science and Technology. Through the introduction of the calligraphy teacher training Curriculum of Shanxi college of Applied Science and Technology, this paper shows readers a special group of Chinese calligraphy teachers, so that readers can generally understand the training requirements, process and curriculum of future calligraphy teachers.From the current situation of curriculum setting, we can also see some problems in the training of Chinese calligraphy teachers. Calligraphy is a unique traditional Chinese art form and a pictographic representation system based on Chinese characters.In the broad and profound Chinese traditional culture and art, the status of calligraphy is unparalleled in the Chinese cultural circle. In China, calligraphy is not only a branch of fine arts, but also has a long history as a unique humanistic wealth, and it still shapes the spiritual world of generations of Chinese people.As an ancient civilization, China has always been praised by the world for its calligraphy. As the carrier of Chinese calligraphy, Chinese characters carry the meaning of cultural inheritance. China has formed a systematic, hierarchical and ideological calligraphy education concept and system, and the understanding, content and implementation methods and approaches of the purpose and meaning of calligraphy education are also being improved and developed. The value and function of calligraphy education also reflects the true nature of Chinese art education.